Nutrient availability affects the response of juvenile corals and the endosymbionts to ocean acidification. (3rd August 2014) - Tanaka, Yasuaki; Iguchi, Akira; Nishida, Kozue; Inoue, Mayuri; Nakamura, Takashi; Suzuki, Atsushi; Sakai, Kazuhiko
Abstract : The interactive effects of nutrient availability and ocean acidification on coral calcification were investigated using post‐settlement juvenile corals of Acropora digitifera cultured in nutrient‐sufficient or nutrient‐depleted seawater for 4 d and then exposed to seawater with different partial pressure of carbon dioxide (PCO 2 ) conditions (38.8 or 92.5 Pa) for 10 d. After the nutrient pretreatment, corals in the high nutrient condition (HN corals) had a significantly higher abundance of endosymbiotic algae than did those in the low nutrient condition (LN corals). The high abundance of endosymbionts in HN corals was reduced as a result of subsequent seawater acidification, and the chlorophyll a per algal cell increased. The photosynthetic oxygen production rate by endosymbionts was enhanced by the acidified seawater regardless of the nutrient treatment, indicating that the reduction in endosymbiont density in HN corals due to acidification was compensated for by the increase in chlorophyll a per cell. Though the photosynthetic rate increased in the acidified conditions for both LN and HN corals, the calcification rate significantly decreased for LN corals but not for HN corals. The acquisition of nutrients from seawater, rather than the increase in alkalinity caused by photosynthesis, might effectively alleviate the negative response of coral calcification to seawater acidification, suggesting that the response of corals and their endosymbionts to ocean acidification can be influenced by nutrient conditions.